2012
DOI: 10.1371/journal.pone.0038847
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated miRNAs in Hereditary Breast Cancer Revealed a Role for miR-30c in Regulating KRAS Oncogene

Abstract: Aberrant miRNA expression has been previously established in breast cancer and has clinical relevance. However, no studies so far have defined miRNAs deregulated in hereditary breast tumors. In this study we investigated the role of miRNAs in hereditary breast tumors comparing with normal breast tissue. Global miRNA expression profiling using Exiqon microarrays was performed on 22 hereditary breast tumors and 15 non-tumoral breast tissues. We identified 19 miRNAs differentially expressed, most of them down-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 34 publications
(46 reference statements)
3
68
0
Order By: Relevance
“…It was previously reported that miR-30c can regulate KRAS in breast cancer (23), and the present study revealed that KRAS was downregulated in miR-30c overexpression cells compared with control cells. This indicated that KRAS may be a common target of miR-30c in different types of tumors.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…It was previously reported that miR-30c can regulate KRAS in breast cancer (23), and the present study revealed that KRAS was downregulated in miR-30c overexpression cells compared with control cells. This indicated that KRAS may be a common target of miR-30c in different types of tumors.…”
Section: Discussionsupporting
confidence: 69%
“…It was previously reported that KRAS is a target of miR-30c in breast cancer (23). The present study aimed to investigate whether miR-30c can control KRAS in prostatic cancer.…”
Section: Mir-30c Regulates the Invasion Of Pc-3 Cells In Vitromentioning
confidence: 93%
“…Let-7a miRNA inhibits cell proliferation in the lung cancer cell line, 95D, by regulating the translation of KRAS mRNA (16). The miRNA miR-30c suppresses breast cancer cell growth, potentially through the inhibition of KRAS signaling (17). Similarly, in coffee extract-treated Caco-2 cells, elevated miR-30c and miR-96 may suppress KRAS expression, potentially by affecting KRAS mRNA stability (17).…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA miR-30c suppresses breast cancer cell growth, potentially through the inhibition of KRAS signaling (17). Similarly, in coffee extract-treated Caco-2 cells, elevated miR-30c and miR-96 may suppress KRAS expression, potentially by affecting KRAS mRNA stability (17). Further studies are needed to clarify the mechanisms underlying regulation of miRNA expression by coffee extract.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that human miRNA-30c was down-regulated in non-small cell lung cancer (NSCLC) and breast cancer [18,19], this informed that miRNA-30c functioned as a tumor suppressor. Quintavalle et al reported that miRNA-30c could suppress apoptosis of lung cancer cells [20].…”
Section: Discussionmentioning
confidence: 99%